A comparative evaluation of the Financial Markets Act 19 of 2012 and the Financial Sector Regulation Bill 2015 with reference to the regulation of insider trading - Delport, P.A. (Piet A.) (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2016.